2017
DOI: 10.1093/ofid/ofx263
|View full text |Cite
|
Sign up to set email alerts
|

Mumps Virus Nucleoprotein and Hemagglutinin-Specific Antibody Response Following a Third Dose of Measles Mumps Rubella Vaccine

Abstract: BackgroundRecent mumps outbreaks among 2-dose measles mumps rubella (MMR) vaccine recipients have raised questions regarding the potential benefits of a third dose of vaccine (MMR3). If MMR3 provides a sustained elevation in mumps antibody, it may be beneficial for certain at-risk groups or as an outbreak control measure.MethodsSera were collected immediately prior to MMR3 and at 1 month and 1 year post-MMR3 from 656 healthy adults aged 18–28 years in a nonoutbreak setting. Immunoglobulin G (IgG) was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Three epidemiologic studies conducted in schools and a university, suggested effectiveness of using MMR3 as public health intervention for mumps outbreak control [ 20 , 21 , 22 ]. Two immunogenicity studies administered MMR3 to subjects aged 18-28 years, demonstrated a significant increase in mumps antibodies one month after vaccination; however antibody titers returned to near-baseline levels a year later [ 23 , 24 ]. In light of the available evidence, a third dose of mumps containing vaccine is recommended in the US only to persons at increased risk for acquiring mumps because of an outbreak [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three epidemiologic studies conducted in schools and a university, suggested effectiveness of using MMR3 as public health intervention for mumps outbreak control [ 20 , 21 , 22 ]. Two immunogenicity studies administered MMR3 to subjects aged 18-28 years, demonstrated a significant increase in mumps antibodies one month after vaccination; however antibody titers returned to near-baseline levels a year later [ 23 , 24 ]. In light of the available evidence, a third dose of mumps containing vaccine is recommended in the US only to persons at increased risk for acquiring mumps because of an outbreak [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our finding of a 6-foldlower antibody titer to the genotype G strain, Rubin et al (26) reported that titers to the genotype G strain in a 2006 mumps outbreak were half those of the Jeryl Lynn strain. Administration of a third MMR dose temporarily boosted antibody titers, but they returned to near-baseline after 1 y (55,57). Epidemiological evidence suggests that a third dose of MMR may have a protective role in outbreak settings (23,54,57).…”
Section: Mumpsmentioning
confidence: 97%
“…Administration of a third MMR dose temporarily boosted antibody titers, but they returned to near-baseline after 1 y (55,57). Epidemiological evidence suggests that a third dose of MMR may have a protective role in outbreak settings (23,54,57). Adding a routine third dose to the current vaccine schedule is feasible to implement (when combined with meningococcal vaccine at age 16), but it does not lead to a sustained increase in antibody responses (57).…”
Section: Mumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies directed against HN have been demonstrated to play a major role in neutralization of the virus (68). However, antibody concentrations against HN were relatively low or below detection levels after MuV infection or vaccination (9, 10). Interestingly, a large fraction of the mumps-specific antibodies is directed against N and can be detected in almost all individuals after vaccination (911).…”
Section: Introductionmentioning
confidence: 99%